The Effect of Using the (K.W.L) Strategy on Developing Inferential Thinking and Performing Some basic Handball Skills for Female Students, College of Education and Sports Sciences, University of Misan - Majid Mohammed Msaed; Esraa AbdulZahr Irkhayyis; Nadia Mahdi Mohammed (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of research is in the use of modern and effective teaching strategies and methods. Therefore,teachers’ ideas tended to find and search for unique teaching methods. The teacher is a guide and assistantto students on the knowledge and how to use educational techniques and strategies that would enable thestudent from storing knowledge and reusing it in new situations. The present study used the (K.W.L.)strategy in developing inductive thinking and learning some basic handball skills and to gain knowledgefrom the theoretical and practical side. As well as this strategy has a new aspect. It is an expressive methodthat supports teachers to achieve the best results. There were statistically significant differences when usingthe (K.W.L.) strategy in developing inferential thinking and learning basic handball skills in the researchsample. The most prominent conclusions reached by the researchers: firstly the (K.W.L.) strategy hasan apparent effect on developing the performance level of the selected basic skills and stimulating thespirit of competition and plays among the students of the research sample. There is a moral correlationbetween learning some basic skills chosen and between developing inductive thinking among the studentsof the research sample. The most prominent recommendations are the adoption of this strategy by facultyprofessors due to the development achieved in the level of performance. Thus, the increase in suspenseand excitement, and the preparation of this strategy can apply for the rest of the games for the same schoolstage and other stages of the study. As well as the possibility of learning and development for students withinferential thinking, teams for universities can be selected from them for various games.